2016
DOI: 10.18632/oncotarget.7156
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 promotes cell migration and invasion but not alters cell proliferation by suppressing E-cadherin, partly through association with MALAT-1 in pancreatic cancer

Abstract: Enhancer of zeste homolog 2 (EZH2) is an essential component of the polycomb repressive complex 2 (PRC2), which is required for epigenetic silencing of target genes, including those affecting cancer progression. Its role in pancreatic cancer remains to be clarified; therefore, we investigated the effects of aberrantly expressed EZH2 on pancreatic cancer. We found that EZH2 expression is up-regulated in pancreatic cancer tissues and positively correlated with lymph node metastasis and advanced clinical stage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 51 publications
0
71
0
Order By: Relevance
“…EZH2 was previously shown to repress E-cadherin in breast, pancreatic and prostate cancer cells [40, 41]. Cooperation between Snail1 and EZH2 in the repression of E-cadherin was also observed during neural crest development [42].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 was previously shown to repress E-cadherin in breast, pancreatic and prostate cancer cells [40, 41]. Cooperation between Snail1 and EZH2 in the repression of E-cadherin was also observed during neural crest development [42].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione‐S‐transferase pull‐down and RIP assays demonstrated that the 3′‐end of MALAT1 interacts with the N‐terminal of EZH2. MALAT1 can mediate tumor progression and chemotherapy resistance by recruiting EZH2 to chromatin loci, such as E‐cadherin, protocadherin 10, p21, and p27 (Han, Jiao et al, ; Hirata et al, ; Qi et al, ; Wang, Ding et al, ; Wang, Zhu et al, ). Malat1 also recruits suppressor of variegation 3‐9 homolog 1 (Suv39h1) to MyoD‐binding loci, causing trimethylation of histone 3 lysine 9 (H3K9me3), which suppresses the transcriptional activity of MyoD, which in turn represses myoblast differentiation (Chen, Zhao et al, ).…”
Section: Mechanisms By Which Malat1 Regulates Biological Functionsmentioning
confidence: 99%
“…1 Its mortality nearly equals its incidence rate, and its overall 5-year survival rate (~8%) has not improved over the last decade. 3,4 Due to these factors and specific anatomical features, only 15-20% of patients are diagnosed with resectable PC, while majority are diagnosed with locally advanced or metastatic disease associated with poor prognosis. 3,4 Due to these factors and specific anatomical features, only 15-20% of patients are diagnosed with resectable PC, while majority are diagnosed with locally advanced or metastatic disease associated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%